Tetanus HUBUNGAN ANTARA STATUS VAKSINASI DENGAN TINGKAT KEPARAHAN TETANUS DI RSUD BANTEN: Studi Retrospektif di Rumah Sakit Umum Daerah Banten Tahun 2022–2024 - Pradyaharini, Zahra Adinda; Irwan Rusmana, Ahmad; Ivana Utami, Louisa (PERDOSNI, 2025)
Introduction: Tetanus is an acute toxemia disease caused by tetanospasmin of Clostridium tetani. The Clinical symptoms of tetanus can be assessed using Phillips score, Dakar Score, and Ablett’s Score. Tetanus is still a public health problem in developed countries due to poor access to immunization. Aim: To analyze the association vaccination status and the severity of tetanus in patients. Method: The study used a retrospective cross-sectional design. Using secondary data from medical records of tetanus patients treated at Banten Regional Hospital during the period 2022 - 2024. Tetanus severity was assessed based on Ablett's Score. The study subjects consisted of a total sampling of all 73 tetanus patients of the year who met the inclusion and exclusion criteria, which were taken using the total sampling technique. Analysis of the relationship between vaccination status and severity was carried out using the Spearman correlation statistical test. Result: A total of 94.5% of patients had no history of tetanus vaccination. In the group of patients without vaccination, 55.1% had severe severity. All vaccinated patients (5.5%) experienced mild symptoms. Statistical test results showed no significant relationship between vaccination status and severity in tetanus patients at Banten Regional Hospital (p – value = 0,079; r = 0,207). Disscussion: There is no statistically significant association between vaccination status and the severity of tetanus (p = 0,079). However, the weak positive correlation (r =0,207) indicates a tendency for more severe symptoms among patients without a complete tetanus vaccination history. Keywords: Tetanus, Tetanus Vaccination, Tetanus Severity, Ablett’s Score